Energy Consumption, Carbon Emissions and Economic Growth in Indonesia and Malaysia - Farabi, Ahmad; Abdullah, Azrai; Setianto, Rahmat Heru (International Journal of Energy Economics and Policy, 2019)
The main objective of this study is to evaluate the relationship between energy consumption, carbon emission and economic growth in the case of Indonesia and Malaysia at the level aggregate and disaggregate. For the model of aggregate energy consumption, this study employ total energy consumption per capita and CO2 emission per capita based on the total of energy consumption. Meanwhile, the disaggregate models use derivatives of variable energy consumption that are oil, coal and gas. Some methodologies of econometrics such as unit root, cointegration, granger causality and error correction model has been employed in this study. The result of unit root test shows that all variables are stationer at first difference and shows the existence of cointegration between the variables. The short and long-run relationship displays that in the both countries, the consumption of all energy source produce CO2 emission and also the increasing of income leads the increasing of CO2 emission. Moreover, gas is less polluting compared with other energy source like oil and coal. In addition, there is a negative relationship between income and carbon emission which means that the carbon emission can be reduced while the income keep growing if both countries use gas as their main energy sources. Keywords: carbon emission, oil, coal, gas, energy consumption, GDP JEL Classifications: K32, P18, Q43, Q48 DOI: https://doi.org/10.32479/ijeep.6573